Highlights from the 2018 European Respiratory Society International Congress: sleep and clinical physiology. Issue 3 (8th July 2019) - Almendros, Isaac; Baillieul, Sébastien; Caballero, Candela; Degani-Costa, Luiza Helena; Furian, Michael; Hirotsu, Camila; Louvaris, Zafeiris; Thiel, Sira; Turnbull, Christopher D.
The 2018 European Respiratory Society (ERS) International Congress held in Paris, France, served as a platform to discover the latest research on respiratory diseases, the improvement in their treatments and patient care. Specifically, the scientific sessions organised by ERS Assembly 4 provided novel insights into sleep disordered breathing and fresh knowledge in respiratory physiology, stressing its importance to understanding and treating respiratory diseases. This article, divided by session, will summarise the most relevant studies presented at the ERS International Congress. Each session has been written by early career members specialised in the different fields of this interdisciplinary assembly. A selection of the best sessions from Assembly 4 at the #ERSCongress 2018 by @EarlyCareerERS http://bit.ly/2Wot0CJ